A new prenylated benzoquinone from Cyathocalyx pruniferus abrogates LPS-induced inflammatory responses associated with PGE2, COX-2 and cytokines biosynthesis in human plasma - Attiq, Ali; Jalil, Juriyati; Husain, Khairana; Jamal, Jamia Azdina; Ismail, Elysha Nur (Springer, 2021)
In our previous laboratory findings, Cyathocalyx pruniferus extracts exhibited platelet-activating factor inhibition, suggesting their anti-inflammatory potential. Hence, this study was designed with the aim to isolate phyto-constituents from C. pruniferus with potent anti-inflammatory activities. Column and volume liquid chromatography were used for isolation of phyto-constituents. The structure elucidation was carried out using spectroscopic analysis (HRESI-MS, 1H and 13C-NMR) and compared with published literature. For cytotoxicity analysis, 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium-bromide assay was performed on peripheral blood mononuclear cells. Anti-inflammatory activities were evaluated against the levels of inflammatory cytokines (IL-1β and IL-6), prostaglandin-E2 (PGE2) and cyclooxegenase-2 (COX-2), in lipopolysaccharide (LPS)-induced human plasma using ELISA and radioimmunoassay (RIA). The chromatographic purification of methanol leaves extract afforded 13 (1-13) secondary metabolites. Additionally, cytotoxicity analysis suggested that isolates were non-cytotoxic at 100 μM. In anti-inflammatory evaluation, 2-octaprenyl-1, 4-benzoquinone (5) produced strong (≥ 70%) inhibition of PGE2, COX-2, IL-1β and IL-6 at 50 µM. Moreover, 2-octaprenyl-1,4-benzoquinone (5) exhibited concentration-dependent inhibition with IC50 values (µM) of 11.21, 6.61, 2.20 and 3.56 as compared to controls; indomethacin for PGE2 (11.84) and dexamethasone in COX-2 (5.19), IL-1β (1.83) and IL-6 (3.76) analysis, respectively. In conclusion, two new compounds including 2-octaprenyl-1, 4-benzoquinone (5) and 14-methyloctadec-1-ene (6) are reported for the first time from plant species. Additionally, 2-octaprenyl-1, 4-benzoquinone (5) dose-dependently suppressed the production of pro-inflammatory mediators involved in acute and chronic inflammation at non-cytotoxic concentrations.